ALGORITMA C4.5 UNTUK PREDIKSI BIMBINGAN SISWA BERDASARKAN TIPOLOGI HIPPOCRATES-GALENUS - Boy Sandy Dwi Nugraha.H; Sarjon Defit; Gunadi Widi Nurcahyo (ITP Press, 2023)
The type of personality possessed by a student belived affect their behavior, whether positively or negatively, and if left unattended, it will harm the student. Student guidance is necessary to provide appropriate guidance for the student. This study aims to predict student guidance based on personality by using student data at SMP 1 Negeri Tembilahan. The data collection process was obtained from the BK teacher at SMPN 1 Tembilahan for grade 8 and grade 7. Grade 8 will be used as training data and grade 7 will be used as testing data. 5 parameters were selected for the prediction process and 1 label as the target class. The method used is the C4.5 algorithm to build a decision tree and obtain prediction rules. The results of the study were obtained using Confusion Matrix testing with a prediction accuracy rate of 70%. The ultimate goal of the student guidance prediction process is to have a higher percentage of